[BOOK REVIEW] The Peaceful Settlement of International Disputes - Davina Oktivana (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
Yoshifumi Tanaka is a Professor of International Law at the Faculty of Law, University of Copenhagen. He has published widely in the fields of the law of the sea and international environmental law. I had a profound admiration for Tanaka’s writings, particularly in law of the sea subjects. He has a compelling method in deliberating issues comprehensively but still convenient to digest, especially for academicians, practitioners, and law students (postgraduate). Settlement of International Dispute is considered as a foundation of the establishment and the development of International Law. Accordingly,  there are plenty of books and writings had published addressing similar topic, however, Tanaka’s book is distinctive. Tanaka successfully gives the reader an exhaustive and extensive analysis  of the procedures for dispute settlement both in traditional means and newly development. In addition, He complemented figures and tables to give the reader a comprehensive understanding.DOI: https://doi.org/10.22304/pjih.v6n1.a11